2004
DOI: 10.1111/j.1553-2712.2004.tb02410.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Household Addresses That Repeatedly Contact 911 to Report Intimate Partner Violence

Abstract: Objectives: To determine whether households that generate several 911 calls differ in important ways from those that make a single call and to determine whether households that generate repeat 911 calls for intimate partner violence (IPV) experience more severe violence than those that do not. Methods: All cases of police‐documented IPV were reviewed and linked with their respective 911 calls. Each incident report was reviewed to determine the relationship between the offender and victim, demographic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Our findings that non-Hispanic black victims were more likely to use police assistance than Hispanic victims, but that white and Hispanic victims had comparable utilization rates, expand upon those of national surveys (Bachman & Coker 1995;Rennison & Welchans 2000) revealing higher reporting rates among black and Hispanic women. A study by Houry et al (2004), however, found reporting patterns similar to ours. Other significant social service utilization patterns in the current study extended only to housing assistance with Hispanic victims less likely than non-Hispanic white or black victims to utilize that service.…”
Section: Discussionsupporting
confidence: 62%
“…Our findings that non-Hispanic black victims were more likely to use police assistance than Hispanic victims, but that white and Hispanic victims had comparable utilization rates, expand upon those of national surveys (Bachman & Coker 1995;Rennison & Welchans 2000) revealing higher reporting rates among black and Hispanic women. A study by Houry et al (2004), however, found reporting patterns similar to ours. Other significant social service utilization patterns in the current study extended only to housing assistance with Hispanic victims less likely than non-Hispanic white or black victims to utilize that service.…”
Section: Discussionsupporting
confidence: 62%
“…In some locales, the numbers may be so high as to comprise more than one half of all calls for service (Klein 2009). Given that so many IPV victims seek help from the police (Friday et al 2006;Hutchison and Hirschel 1998), and that many do so repeatedly (Friday et al 2006;Houry et al 2004), it is important that agencies focus and dedicate as much time and resources to IPV as they do to other major crimes (Klein 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Among opposite-sex couples who experience at least one IPV incident in the previous year, 40% of the incidents involve kicking, punching, strangling, or stabbing (Straus and Gelles 1999). Although most incidents of intimate partner victimizations are not reported to the police (Tjaden and Thoennes 2000), many victims have called the police (Bachman and Saltzman 1995;Brookoff et al 1997;Chaudhuri and Daly 1992; Hutchison and Hirschel 1998), many multiple times (Houry et al 2004).…”
Section: Incident Characteristics and Implications For Public Health mentioning
confidence: 99%
“…Some people, however, make numerous calls to crisis helplines over defined periods. These callers have been termed 'frequent' (Haycock, 1997;Leuthe and O'Connor, 1980), 'chronic' (Barmann, 1980;Bartholomew and Olijnyk, 1973;Bassuk and Gerson, 1980;Brockopp, 1970;Greer, 1976;Imboden, 1980;Lester and Brockopp, 1970;Sawyer and Jameton, 1979;Speer, 1971), and'repeat' (Hall andSchlosar, 1995;Houry et al, 2004) callers. In this paper, we use the nomenclature 'frequent callers' to describe them.…”
Section: Introductionmentioning
confidence: 99%